ANALISIS HUBUNGAN PAPARAN DEBU DENGAN KAPASITAS VITAL PARU PADA PEKERJA BAGIAN PRODUKSI PT. X TAHUN 2023 - La Rose Sekar Langit, (2023)
The carpet production process at PT. X has generated dust which may affect respiratory distress. Exposure to the resulting dust can cause occupational diseases, especially in the lungs. The purpose of this study was to analyze the dust exposure and lung vital capacity of workers in the production department. The research method used is a quantitative method with a cross-sectional design. The sampling technique is non-probability sampling and 88 respondents were taken purposively Sources of data used in this study were a questionnaire, a spirometer, and an air quality index monitor. After the data is collected, it is analyzed by the chi-square test. 85.2% of workers experienced a decrease in lung vital capacity. There is a relationship between years of service (p-value=0.032) and the use of protective equipment (p-value=0.016). Exposure to dust in the work environment has no significant relationship with lung vital capacity. It is hoped that workers will adopt the habit of using personal protective equipment masks while maintaining physical health, while companies can install exhaust fans and carry out administrative controls such as doing work rotations.